Bird responses to riparian management of degraded lowland streams in southeastern Australia. Issue 2 (8th December 2014) - Hale, Robin; Reich, Paul; Johnson, Matthew; Hansen, Birgita D.; Lake, Phillip S.; Thomson, James R.; Mac Nally, Ralph
<x xml:space="preserve">Abstract</x> We assessed the degree to which fencing, livestock exclusion, and replanting of riparian zones affected avian assemblages in massively cleared landscapes. Measurements were made at three creeks in the southern Murray–Darling Basin in southeastern Australia, each of which had circa 1‐km long treated sections and paired "untreated" circa 1‐km sections, where no fencing, planting, or stock exclusion was done. We measured the change in vegetation characteristics and abundances of native birds for up to 8 years after works were completed. Prior to data collection, we developed expected responses of bird species based on the anticipated time‐courses of change in vegetation structure. We used hierarchical Bayesian models to explore the effects of the management actions, and to account for within‐site variation in vegetation characteristics. There were major changes in vegetation structure (reductions in bare ground and increases in shrubs and tree recruitment) but avian responses generally were small and not as expected. There are at least four possible reasons for the limited avian responses: (1) there has been a long‐term decline in woodland birds across the region; (2) the study was conducted during the longest drought in the instrumental record in the study region; (3) the total amount of replanted vegetation was small in a massively denuded region; and (4) monitoring may have been over too short a term to detect responses to longer‐term changes in structural vegetation.